KEPERLUAN E-MODUL FISIKA BERBASIS PROBLEM BASED LEARNING UNTUK MELATIH PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI DINAMIKA PARTIKEL - Jihan Pransiska; M. Rahmad M. Rahmad; Zulhelmi Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this research was to analyze the need for developing teaching materials in the form of PBL-based physics e-modules that can assist students in training their understanding of concepts in particle dynamics material during learning. This type of research is descriptive research. In this research there were subjects consisting of 21 students in class XII MIPA 4 at SMA Negeri 9 Pekanbaru with various cognitive abilities from high, medium and low. The research data was obtained through observation, direct interviews and the distribution of positive response questionnaire links through the Google Form. The results of data collection explained that (1) the learning outcomes of physics subjects mostly did not reach the minimum completeness criteria (KKM) determined by the school, (2) there were obstacles experienced by students in achieving scores above the KKM including limited physics books, difficult to remember physics formulas, and many assignments other than physics subjects, (3) the learning media used is only in digital form not online (pdf) and digital online (google form), (4) students need easy online physics-based learning media understood and interesting so that it is more excited. The results of the needs analysis show that an online-based physics learning media needs to be developed in the form of a PBL-based physics e-module to train students' conceptual understanding of particle dynamics material at the SMA/MA equivalent level.Keywords: Requirements Analysis, E-Module, PBL, Concept Understanding.